PRIVACY BY DESIGN SEBAGAI INSTRUMEN PERLINDUNGAN KONSUMEN: INTEGRASI ISO 31700-1:2023 KE DALAM REGULASI PRODUK & LAYANAN DIGITAL DI INDONESIA - Rahmi Rahmi; Zainal Said; Rezky Hidayah; Nur Ali Padengka; Nursyamsi Mahmud; Ririn Pratiwi (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the implementation of the Privacy by Design concept as an instrument of digital consumer protection in Case Number 235/Pdt/G/2020/PN.Jkt.Pst concerning the Tokopedia data breach, as well as to examine the relevance of integrating ISO 31700-1:2023 standards into Indonesian digital regulations. This research employs a normative legal method using statutory, case, and conceptual approaches. Legal materials were collected through library research consisting of laws and regulations, court decisions, academic journals, and international standards related to personal data protection. The findings indicate that the implementation of Privacy by Design principles in Indonesia’s digital systems has not been fully optimized. This is reflected in weak data security protection, limited user control over personal data, and regulatory approaches that remain reactive in nature. Although the Personal Data Protection Law has provided a stronger legal framework, the implementation of privacy by default principles and system design-based protection still requires more concrete technical regulations. This study concludes that integrating Privacy by Design principles and ISO 31700-1:2023 standards is essential to strengthen digital consumer protection, enhance personal data security, and create a safer, more transparent, and consumer-oriented digital ecosystem.